Sistem Pendukung Keputusan Pemilihan Tablet PC Menggunakan Metode WASPAS dan MOORA - Syam, Syahriani; Waworuntu, Alexander; Ayuningtyas, Astika; Harun, Rofiq; Nadjamuddin, Lukman (Forum Kerjasama Pendidikan Tinggi, 2023)
Tablet Pc is a personal computer with a portable design that is equipped with a main input device, namely a touch screen and is designed for individual use. The use of the screen as an input intermediary can use a fingertip and a digital pen. Thus making the production of personal tablet pc increasingly improve its quality so as not to lose competitiveness. Decision Support System is a computer-based information system created to determine decisions so that they are more in solving problems that are structured and unstructured, so the resulting decisions are more appropriate. The system created is a system by utilizing the WASPAS and MOORA methods. A system that utilizes the WASPAS and MOORA methods so that it is suitable in determining the best type of Tablet PC. So the one that gets the title of the best Tablet PC is the A1 alternative with the name Samsung Galaxy Tab S8 Ultra with the value for the WASPAS method, which is 0.456, while the MOORA method is 0.439 as the best alternative